Earnings management in the process of preparing corporate financial reports - Kepsu, Mikko (fi=Turun yliopisto|en=University of Turku|, 2012)
Earnings management (EM) literature examines managers’ use of judgment in financial reporting and in structuring transactions to alter financial reports for a specific reason. Mainstream EM literature strongly concentrates on statistical research methodologies and it is driven by positive accounting theory. Although EM occurs in the process of preparing corporate financial reports, that process has so far largely remained a “black box” in prior literature. The purpose of this study is to analyze what EM is, how and why it unfolds and how it is intertwined in the process of preparing corporate financial reports. In order to meet the needs of the study, a qualitative case study method will be used. The contribution of this study is threefold. First, it indicates that the concept of EM is not as unam-biguous as the prior literature has assumed. I find that EM is socially constructed and more open to interpretation than absolutely dichotomous conception given by previous studies. Second, this study contributes to our knowledge of the role and the importance of actors involved in conducting EM, indicating that EM is much more actor-dependent than the prior literature has assumed. Third, this study broadens our knowledge base with regard to the processes and potential for EM in academic research.